أثر منهج تأهيلي للاعبين المصابين في مفصل الكاحل بكرة اليد المتقدمين - عبدالحسين، ليث محمد; الهلالي، حسن هادي عطية (جامعة بابل - كلية التربية الرياضية, 2021)
تتجلى أهمية البحث في اعداد منهج تأهيلي، اذ يعتقد الباحث انها ستحدث تأثيراً في المدى الحركي والعضلات والاربطة المحيطة بمفصل الكاحل وإرجاعه للعمل بوضعه الطبيعي أو شبه الطبيعي للاعبين المصابين في مفصل الكاحل بكرة اليد المتقدمين، لذا رغب الباحث الخوض في هذه التجربة. أما مشكلة البحث: من خلال خبرة الباحثان ومراجعة الكثير من الدراسات والبحوث لاحظا كثرة حدوث إصابة مفصل الكاحل وتكرارها لدى لاعبي كرة اليد مما يدفع أغلب المصابين الى مراجعة الأطباء لغرض علاج الإصابة كما لاحظا الباحثان أن البرنامج المتبع في الطب التقليدي يستغرق فترة طويلة في علاج وتأهيل الرياضيين المصابين بالإضافة الى افتقاره الى الوسائل الحديثة في تأهيل هذه الاصابة. لذا ارتأى الباحثان دراسة هذه المشكلة ووضع الحلول المناسبة لها من خلال أعداد منهاج تأهيلي مبني على أسس علمية سليمة ومتضمنا بعض التمرينات التأهيلية كوسيلة تأهيلية للمصابين لإعادة تأهيل العضلات المصابة وإعادة المدى الحركي الطبيعي والقوة لمفصل الكاحل. وقد هدف البحث الى: إعداد منهج تأهيلي للاعبين المصابين في مفصل الكاحل بكرة اليد المتقدمين، كذلك التعرف على تأثير المنهج التأهيلي في المدى الحركي وقوة العضلات المحيطة للاعبين المصابين في مفصل الكاحل بكرة اليد المتقدمين. أما عن منهجية البحث وإجراءاته الميدانية، فاستخدم الباحث المنهج التجريبي في حل مشكلة البحث، اما مجتمع البحث فقد تم تحديد مجتمع البحث باللاعبين. تم تحديد مجتمع البحث باللاعبين المتقدمين المصابين بالتواء مفصل الكاحل لأندية الفرات الأوسط لأندية المشاركين بالدوري العراقي الممتاز بكرة اليد للموسم الرياضي 2020- 2021 وهم (كربلاء، القاسم، الدغارة، الكوت) ممن يعانون من إصابة التمزق الجزئي البسيط لأربطة مفصل الكاحل، اذ تم اعتماد الإصابة للاعبين من خلال معالج الفريق، فضلاً عن التشخيص بواسطة طبيب مختص والبالغ عددهم (5) لاعبين، وتم اختيارهم بالكامل للتجربة. أما عن أهم الاستنتاجات: إن المنهج التأهيلي المقترح كان له الدور الفاعل في تحسن زوايا المدى الحركي لمفصل الكاحل، إن المنهج التأهيلي عزز إيجابيا وبشكل كبير جداً الجانب المعنوي والنفسي والذي يعد عاملاً مساعداً في تسريع الشفاء من الإصابة. The importance of the research is manifested in preparing a rehabilitation curriculum, as the researcher believes that it will affect the range of motion, muscles and ligaments surrounding the ankle joint and return it to work in its normal or semi-natural position for players injured in the ankle joint with the handball advanced, so the researcher wanted to delve into this experiment. As for the research problem: through the experience of the researchers and reviewing many studies and research, they noticed the frequent occurrence of ankle joint injury and its recurrence among handball players, which leads most of the injured to refer to doctors for the purpose of treating the injury. The researchers also noted that the program followed in traditional medicine takes a long time to treat and rehabilitate athletes In addition to his lack of modern means to rehabilitate this injury. Therefore, the researchers decided to study this problem and develop appropriate solutions to it through preparing a rehabilitation curriculum based on sound scientific foundations and including some rehabilitation exercises as a means of rehabilitation for the injured to rehabilitate the injured muscles and restore the normal range of motion and strength for the ankle joint. The research aimed at: preparing a rehabilitation curriculum for advanced handball players with ankle joint injuries, as well as identifying the effect of the rehabilitation curriculum on the range of motion and the strength of the surrounding muscles for advanced handball players. As for the research methodology and field procedures, the researcher used the experimental method to solve the research problem. As for the research community, the research community was determined by the players. The research community was identified with the advanced players with sprained ankle of the middle Euphrates clubs for the participating clubs in the Iraqi Premier League handball for the sports season 2020- 2021, and they are (Karbala, Al-Qasim, Al-Daghara, Al-Kut) who suffer from a simple partial rupture of the ankle joint ligaments, as the injury was approved For players through the team therapist, in addition to the diagnosis by a specialist doctor, the number of (5) players, and they were completely selected for the experiment. As for the most important conclusions: The proposed rehabilitation approach had an active role in improving the angles of movement range of the ankle joint. The rehabilitation approach has positively and greatly enhanced the moral and psychological aspect, which is a conducive factor in accelerating recovery from injury.
Keywords: التأهيل الرياضي -- الإصابات الرياضية -- لاعبو كرة اليد